Dietary and Exercise Behaviour of Secondary School Girls in Rural and Urban Settings - Adhikary, Anamica; Haque, Md Jawadul; Amin, Md Nurul; Podder, Shaon Kumar (Ibrahim Cardiac Medical Journal, 2023)
Background & objective: The increasing prevalence of unhealthy eating habits and sedentary lifestyles among adolescents, which often continues into adulthood, is a global public health problem. Many studies have so far addressed the nutritional status, dietary and exercise behaviour of the urban adolescents. But there are few studies which compared the nutritional status, dietary and exercise behaviour of the rural adolescent girls with those of urban adolescent girls. The present study was aimed to make a comparative evaluation of food and exercise behaviour of secondary school girls between rural and urban settings. Methods: This cross-sectional analytical study was conducted in the Department of Community Medicine, Rajshahi Medical College, Rajshahi over a period of 12 months from January 2019 to December 2019. The data for the study were collected from 314 adolescent girls (from class 6 to class 10) from two secondary girls’ school of Kushtia, namely Panti Girls High School, a rural school and Kushtia Govt. Girls High School an urban school. Of the 314 girls (respondents), 140 were rural and 174 were urban residents. Students 1) having known chronic diseases like valvular heart diseases or any other systemic diseases that may affect their nutritional status, 2) absent on the day of interview and 3) who refused to participate in the study were excluded. Data were collected from the respondents using a semi-structured questionnaire containing the variables of interest. Result: The age of the respondents of secondary school girls ranged from 11 to 17 years with mean age being nearly 14 years in both rural and urban cohorts. Urban adolescent girls were heavier than their rural counterparts (22 and 20.9 kg/m² respectively). The predominant indoor and outdoor exercises adopted by rural and urban girls were jumping rope and walking respectively. While urban adolescent girls used to skip rope more commonly, rural girls prefer riding a bicycle and running as outdoor exercises more often than the urban girls. One-third (32.1%) of the rural girls and 17% of the urban girls met the WHO criteria of physical activity/exercise. Rural girls frequently watch TV, while urban girls prefer playing games or surfing social media on mobile or computer as a pastime. Besides, the urban girls were more often fond of listening music, reading a book and gardening compared to their rural counterparts with majority of the urban girls spent > 1 hour each day on mobile/TV/computer. About 90% of the urban girls used to having breakfast more or less regularly as compared to 77% of the rural girls. Practice of taking major meals > 2 times a day was significantly higher in the rural group than that in the urban group. However, taking light meals or snacks ≥ 2 times a day was much higher among urban respondents. Consuming milk, eggs and meat in most of the days in a week were frequently practised by the urban girls than that by the rural girls. Although intake of vegetables was almost identical between the groups, consumption of fruits was much higher in the urban girls than that in the rural girls. There was significant association between dietary habit and residence with more than 55% of the rural adolescent girls having unhealthy dietary behaviour as opposed to 41% of urban girls. The odds of having unhealthy dietary behaviour were nearly 2-fold (95% CI = 1.2-2.9) higher in rural girls than that in urban girls. Conclusion: The study concluded that urban adolescent girls are usually heavier than the rural girls. About one in three rural girls and one in six urban girls meet the WHO criteria of physical activity/exercise suggesting that rural girls are more inclined to have good exercise behaviour than do their urban counterparts. A significant association between dietary habit and residence is observed with risk of having unhealthy dietary behaviour in rural girls is nearly double than that of urban girls. Ibrahim Card Med J 2021; 11 (2): 62-68